Risk factors for respiratory work disability in a cohort of pulp mill workers exposed to irritant gases - Torén Kjell; Murgia Nicola; Kim Jeong-Lim; Andersson Eva (BMC, 2011)
Abstract Background The association between chronic respiratory diseases and work disability has been demonstrated a number of times over the past 20 years, but still little is known about work disability in occupational cohorts of workers exposed to respiratory irritants. This study investigated job or task changes due to respiratory problems as an indicator of work disability in pulp mill workers occupationally exposed to irritants. Methods Data about respiratory symptoms and disease diagnoses, socio-demographic variables, occupational exposures, gassing episodes, and reported work changes due to respiratory problems were collected using a questionnaire answered by 3226 pulp mill workers. Information about work history and departments was obtained from personnel files. Incidence and hazard ratios for respiratory work disability were calculated with 95% confidence intervals (CI). Results The incidence of respiratory work disability among these pulp mill workers was 1.6/1000 person-years. The hazard ratios for respiratory work disability were increased for workers reporting gassings (HR 5.3, 95% CI 2.7-10.5) and for those reporting physician-diagnosed asthma, chronic bronchitis, and chronic rhinitis, when analyzed in the same model. Conclusions This cohort study of pulp mill workers found that irritant peak exposure during gassing episodes was a strong predictor of changing work due to respiratory problems, even after adjustment for asthma, chronic bronchitis, and chronic rhinitis.